2017
DOI: 10.1016/j.hemonc.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Study of CD4+, CD8+, and natural killer cells (CD16+, CD56+) in children with immune thrombocytopenic purpura

Abstract: ITP is associated with immunity dysfunction denoted by the increase in cytotoxic T lymphocytes and the decrease in natural killer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 31 publications
4
7
1
Order By: Relevance
“…In our study, we found that NK cells were significantly decreased in active ITP patients than in controls. This was in agreement with Talaat et al [16] and El-Rashedi et al [10]. For ITP patients who had undergone therapy, Garcia-Suarez, et al found that the activity of NK cells was correlated with therapy treatment, meaning that there was an increase in the number of NK cells in ITP patients who were effectively treated [17].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In our study, we found that NK cells were significantly decreased in active ITP patients than in controls. This was in agreement with Talaat et al [16] and El-Rashedi et al [10]. For ITP patients who had undergone therapy, Garcia-Suarez, et al found that the activity of NK cells was correlated with therapy treatment, meaning that there was an increase in the number of NK cells in ITP patients who were effectively treated [17].…”
Section: Discussionsupporting
confidence: 83%
“…Abnormal T-lymphocyte subpopulations in patients with ITP have been previously reported. Some studies have reported increased CD8+ T lymphocytes and decreased CD4/CD8 ratios [10]. Other reports, however, have indicated normal CD4/CD8 ratios [11][12][13], increased numbers of both CD4+ T and CD8+ T lymphocytes [12,14], or decreased CD8+ T lymphocytes alone in patients with ITP [15].…”
Section: Discussionmentioning
confidence: 99%
“…The CD3 − CD56 + NK cells count was diminished in the UT‐ITP and NR‐ITP groups. El‐Rashedi et al () also observed a significant reduction in the percentage of NK cells in patients with ITP compared with healthy controls, with a maximum reduction in the acute form of the disease. Conversely, Garcia‐Suarez et al () reported increased CD3 − CD56 + NK cells in ITP patients, particularly in those refractory to therapeutic treatments.…”
Section: Discussionmentioning
confidence: 90%
“…38 Subsequently, Ebbo et al 39 demonstrated that NK cytotoxicity was also suppressed in spleen cells from patients with ITP. More recently, El-Rashedi et al 40 examined NK cells in children with ITP and concluded that childhood ITP is associated with an increase in cytotoxic T lymphocytes, but a decrease in peripheral blood NK cells. The reasons for these observations are unclear, particularly since patients with ITP have elevated levels of interferon-g which is predominantly produced by NK cells.…”
Section: Nk and T Lymphocyte Dysregulationmentioning
confidence: 99%